COMPARATIVE ANALYSIS OF STANDARDS AND REGULATORY DOCUMENTS FOR LONG-TERM PRESERVATION AND VALIDATION OF ELECTRONIC DOCUMENTS AND SIGNATURES - Okhrimenko, Andrew; Stokipnnyi, Oleksandr; Kovtun, Vladislav (Ukrainian Information Security Research Journal, 2025)
The article provides a comparative analysis of international, European and Ukrainian standards and regulatory documents governing long-term preservation of electronic documents and long-term validation of electronic signatures. The regulatory landscape is systematized at three levels: global (OAIS/ISO 14721, ISO 16363, IETF RFC 4998/6283, AdES formats), European (eIDAS 1.0/2.0, ETSI EN 319 series, TR-ESOR, NF Z42-013, E-ARK), and national (Ukrainian Law on Electronic Trust Services, Ministry of Justice Order No. 1886/5 as amended in 2025, e-Archive pilot). Key differences in the depth of legal regulation, maturity of trust service infrastructure, and practical application of LTV mechanisms are identified.